Equitable multilingualism? The case of Stellenbosch University Writing Laboratory - Daniels, Sharifa; Richards, Rose (Stellenbosch Papers in Linguistics Plus, 2017)
This article reflects on Stellenbosch University Writing Lab’s pedagogical approach to multilingualism and inclusivity within the complex and political nature of multilingual language policies at a South African university. The Writing Lab has always been promoted as a facility for all students, not just those in need of ‘remedial’ support. This was a departure from earlier academic literacies models that tended to view students from nondominant language groups in terms of deficits. Academic literacies research has pointed to the shortcomings of these earlier approaches and to the value conflicts that arise from them. We, in contrast, argue that Carter’s (2009) writing centre paradox provides a dynamic rhetorical space in which to explore issues around South African multilingualism and inclusivity in higher education, and for this reason we do not wish to resolve the paradox. Instead, we use it to critically appraise our type of equitable multilingualism and maintain and honour multivocality. We also argue that South African writing centres enjoy a somewhat different trajectory from that of many other academic literacies spaces by virtue of the one-to-one pedagogy and mutualistic approach we follow at these writing centres. This has allowed us simultaneously more agency and less agency and we need to use this paradoxical position strategically in our institutions. Using the Writing Lab as a case study, we reflect on the ways in which the Writing Lab gives life to its ethos of being a multilingual and inclusive space for academic transformation within the institution’s language policy. To support our reflections, we draw on descriptions of the organisational structure of the Lab, feedback received from strategic role players and observations of interactions performed in the various Lab spaces. We also consider the Writing Lab in terms of South African writing centre scholarship to see how the Lab’s philosophy and ethos compare with the ideals.